Penguatan Peran Orang Tua melalui Pola Asuh Demokratis dalam Menekan Kasus Bullying di SDN Sempu Kecamatan Ngebel Kabupaten Ponorogo - Siti Nur Haliza; Fauza Ni'amatul Mubarokah (Social Science Academic, 2025)
This study aims to strengthen the role of parents through the application of democratic parenting in reducing bullying cases at SD Negeri Sempu, Ngebel District. Democratic parenting is considered an effective approach to shaping children’s character to be empathetic, cooperative, and self-controlled, thereby preventing the emergence of bullying behavior. The research employed the Asset-Based Community Development (ABCD) approach, which consists of the stages of discovery, dream, design, and define/deliver. Data were collected through semi-structured interviews, participatory observation, focus group discussions (FGD), activity documentation, and a parenting program trial. Data analysis was conducted using a descriptive qualitative method based on the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing. The findings indicate that parents are the primary asset in preventing bullying, both individually and as part of the school community. The implementation of democratic parenting has been proven to increase parental knowledge and awareness, improve family communication, and foster children’s social–emotional skills. At the school level, the program’s implementation has contributed to a decrease in reported bullying cases and the creation of a more conducive learning environment.